1972
DOI: 10.1130/0016-7606(1972)83[3675:eaccoe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Epeirogenic and Climatic Controls of Early Pleistocene Fluvial Sediment Dispersal in Nebraska

Abstract: The change from Pliocene to Pleistocene fluvial sedimentation in Nebraska is denoted by gravel with relative enrichment of mechanically weak rock species and a two-fold increase in largest clast size. These changes in fluvial sediments suggest modification in degradational energy affecting detritus apparently related to deterioration of climate in the early Pleistocene. Cooler Pleistocene climates with increased moisture resulted in greater discharge and carrying capacity for streams headed in the Rocky Mounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
0
38
1
Order By: Relevance
“…Measurements made on the ten largest clasts by Breyer (1974Breyer ( , 1975 and by Swinehart (1979) generally are lower than those reported earlier by Stanley and Wayne (1972) at the same sample sites. A field check at the sites supported the values cited in the later reports.…”
Section: Generalization 2 Single Cycle Of Erosion and Depositioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Measurements made on the ten largest clasts by Breyer (1974Breyer ( , 1975 and by Swinehart (1979) generally are lower than those reported earlier by Stanley and Wayne (1972) at the same sample sites. A field check at the sites supported the values cited in the later reports.…”
Section: Generalization 2 Single Cycle Of Erosion and Depositioncontrasting
confidence: 39%
“…Distinctive Gravel Sizes and Mineralogies Stanley (1971) and Stanley and Wayne (1972) believed that Ogallala gravels could be separated from post-Ogallala gravels in western Nebraska, and they made a number of assertions related to the general topics of sediment dispersal, source areas, and stream competence for Ogallala and early Pleistocene gravels. Stanley and Wayne (1972) stated that Ogallala gravels in western Nebraska .are generally free of anorthosite, that with a few exceptions the presence of anorthosite and larger clast size may be used to separate early Pleistocene from Ogallala gravels, and that the main early Pleistocene drainage way in the Nebraska Panhandle was through the ancestral Pumpkin Creek Valley. They also concluded that Pleistocene streams were more competent than Ogallala streams in western Nebraska.…”
Section: Generalization 2 Single Cycle Of Erosion and Depositionmentioning
confidence: 99%
“…These sediments, from sources in central Wyoming and northern Colorado ( fig. 1) (Stanley and Wayne, 1972) are unevenly deposited and preserved but contain coarse sand and gravel separated by finer-grained deposits covering the Ogallala in much of the upper Loup study area. Pliocene and Pleistocene fluvial deposits average 50 ft (15 m) in thickness, but can be as thick as 300 ft (91 m) (Swinehart and Diffendal, 1989), and are in hydrologic connection with the underlying Ogallala.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Abbreviations of USA states are: Colorado (CO), Iowa (IA), Kansas (KS), Nebraska (NE), New Mexico (NM), Oklahoma (OK), South Dakota (SD), Texas (TX), Wyoming (WY). Stanley and Wayne, 1972;Witzke and Ludvigson, 1990) suggest that late Miocene drainages with paleo-headwaters in the Rockies continued from present-day Nebraska across Iowa and into the ancestral Mississippi River (Figure 2). …”
Section: Introductionmentioning
confidence: 99%